Contribution of Arginine Catabolic Mobile Element and Copper and Mercury Resistance Element in Methicillin-Resistant Staphylococcus aureus: A Vantage Point - Parya Shokrollahi; Alka Hasani; Mohammad Aghazadeh; Mohammad Yousef Memar; Akbar Hasani; Maryam Zaree; Mohammad Ahangarzadeh Rezaee; Javid Sadeghi (Canadian Journal of Infectious Diseases and Medical Microbiology)
Different clones of community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) are dominating geographically. One of the significant, hypervirulent, CA-MRSA and a significant health concern clones is USA3000, found worldwide regionally with varying frequencies. The clone harbors several mobile genetic elements (MGEs) including, arginine catabolic mobile element (ACME) and copper and mercury resistance genes (COMER), accomplished by horizontal gene transfer from S. epidermidis. Evidence suggests that ACME and COMER have a more prominent role in enhancing biofilm capacity and ultimately persistent infections. This review highlights the comprehensive view on ACME and COMER structure, their distribution, and the mechanism of action along with pathogenetic features of USA3000 encompassing their role in biofilm formation, adhesion, quorum sensing, resistance to antibiotics, chemotaxis, and nutrient uptake. We also provided an insight into the role of ACME and COMER genes in the survival of bacterium. Our results shed light on the emergence of two independent clones possessing ACME (North American) and COMER (South American) elements which later disseminated to other regions. ACME and COMER both are adjacent to staphylococcal cassette chromosome mec type IV (SCCmec IV). The acquisition of mecA, followed by COMER or ACME has been shown as a significant factor in the rise and fall of MRSA strains and their complex ability to adapt to hostile environments. The presence of ACME increases fitness, thereby allowing bacteria to colonize the skin and mucous membrane while COMER contributes to genetic stability by knocking over the copper-mediated killing in macrophages. Evidence suggests that ACME and COMER have a more prominent role in enhancing biofilm capacity and ultimately persistent infections. Interestingly, ACME strains have been shown to possess the ability to counteract skin acidity, thereby allowing increased skin colonization. A profound understanding of MGEs in S. aureus plays an important role in the prevention of epidemic clones.